Pollen analysis of postglacial sediments from Eildun Lake, District of Mackenzie, N.W.T., Canada - Slater, Donald S. (Canadian Journal of Earth Sciences, 1985)
Sediment from Eildun Lake, located at 63°8.6′N, 122°46.5′W in the northern boreal forest, was cored to a depth of 268 cm and analyzed for pollen content. Pollen percentages and 14 C dates suggest a vegetational sequence extending back over 11 000 years. The sequence begins with a discontinuous herb tundra dominated by Artemisia and Gramineae. This was succeeded by a shrub tundra dominated by dwarf birch and willow. Poplar had invaded by approximately 10 700 BP to form a dwarf birch – poplar groveland or forest tundra. Between approximately 10 300 and 7510 BP spruce replaced poplar as the dominant tree, although still forming a forest tundra. Boreal forest, including tree birch and alder, became established shortly after 7510 BP and has persisted since then with very little change. Pinus pollen has increased in percentage, particularly during the last 2400 years, reaching its Holocene maximum at the present day. The percentages attained indicate the presence of pine trees regionally though not in the near vicinity of Eildun Lake.